Cladodes from prickly pear as a functional ingredient: effect on fat retention, oxidative stability, nutritional and sensory properties of cookies. (17th November 2015) - Msaddak, Lotfi; Siala, Rayda; Fakhfakh, Nahed; Ayadi, M. A.; Nasri, Moncef; Zouari, Nacim
Abstract: The stems of Opuntia ficus - indica known as cladodes are rich source of bioactive and functional substances, which make them important candidate for the production of health-promoting food. Cladodes powder was incorporated at different levels of substitution (2.5%, 5% and 7.5%) in cookies (butter/wheat flour: 55/100 m/m). Substitution of wheat flour by cladodes powder improved dietary fiber, ash, potassium, magnesium and calcium contents of enriched cookies. The results also revealed that cladodes supplementation increased hardness; however, it decreased a* and b* values and reduced exudate loss of cookies during storage. Moreover, rising levels of cladodes powder contribute to the increase of antioxidant activity of cookies and decreased their oxidative degradation. Sensory evaluation showed that cladodes supplementation at 5% level remained acceptable at 5-point hedonic scale. The present study suggested that cladodes supplementation in high-fat cookies not only added nutritional value to food, but also improved its functional characteristics.